Electrical transport and EPR properties of the α, β, and γ phases of Fe2WO6 - Guskos, N.; V. Likodimos; Glenis, S.; Patapis, S.K.; Palilis, L.C.; Typek, J.; Wabia, M.; Rychlowska-Himmel, I. (Physical Review B - Condensed Matter and Materials Physics, 1999)
The polymorphic modifications α, β, and γ phases of Fe2WO6 of the iron (III) tungstate have been investigated by resistivity and electron paramagnetic resonance (EPR) measurements. The high-electrical resistivity for all phases complies with the dominant antiferromagnetic component of the compounds. The EPR spectra comprise a broad exchange narrowed EPR line due to Fe3+ ions. The broadening of the EPR linewidth is explained in terms of the critical spin fluctuations near the antiferromagnetic phase transition. The shift of the resonance field and the temperature dependence of the EPR intensity imply an extended region of short-range order correlations. © 1999 The American Physical Society.
cited By 9